2009
DOI: 10.1016/j.schres.2009.03.020
|View full text |Cite
|
Sign up to set email alerts
|

An upregulation of DNA-methyltransferase 1 and 3a expressed in telencephalic GABAergic neurons of schizophrenia patients is also detected in peripheral blood lymphocytes

Abstract: Several lines of schizophrenia (SZ) research suggest that a functional downregulation of the prefrontal cortex GABAergic neuronal system is mediated by a promoter hypermethylation, presumably catalyzed by an increase in DNA-methyltransferase-1 (DNMT-1) expression. This promoter hypermethylation may be mediated not only by DNMT-1 but also by an entire family of de novo DNA-methyltransferases, such as DNA-methyltransferase-3a (DNMT-3a) and -3b (DNMT-3b). To verify the existence of an overexpression of DNMT-3a an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 31 publications
(62 reference statements)
11
76
1
3
Order By: Relevance
“…Consistent with this hypothesis, patients with schizophrenia exhibit hypermethylation at the synaptic plasticity gene reelin in the cortex, which is associated with decreased reelin expression (Grayson et al, 2005). Additionally, post-mortem samples from schizophrenic patients have revealed an overexpression of DNMT1 and DNMT3a in GABAergic neurons (Zhubi et al, 2009), which is consistent with the observation that DNMT1 regulates reelin methylation in vivo (Noh et al, 2005).…”
Section: Dna Methylation In Schizophreniasupporting
confidence: 61%
“…Consistent with this hypothesis, patients with schizophrenia exhibit hypermethylation at the synaptic plasticity gene reelin in the cortex, which is associated with decreased reelin expression (Grayson et al, 2005). Additionally, post-mortem samples from schizophrenic patients have revealed an overexpression of DNMT1 and DNMT3a in GABAergic neurons (Zhubi et al, 2009), which is consistent with the observation that DNMT1 regulates reelin methylation in vivo (Noh et al, 2005).…”
Section: Dna Methylation In Schizophreniasupporting
confidence: 61%
“…While several studies from our group have pointed to a hypermethylating milieu in the brains of psychotic subjects (Grayson et al, 2005;Guidotti et al, 2011Guidotti et al, , 2007Veldic et al, 2005Veldic et al, , 2007Zhubi et al, 2009;Ruzicka et al, 2007), others found decreased DNA methylation at particular genes (Abdolmaleky et al, 2006) or overall dysfunctional methylation networks comprised of both increases and decreases in methylation (Mill et al, 2008). Further, several studies have failed to replicate DNA methylation changes at particular genes (Tochigi et al, 2008;Mill et al, 2008;Dempster et al, 2006).…”
Section: Gadd45b and Psychosis Dp Gavin Et Almentioning
confidence: 87%
“…This is because the majority of previous studies have reported increases in factors associated with a restrictive chromatin state, such as increased DNMT expression (Veldic et al, 2004(Veldic et al, , 2005Zhubi et al, 2009;Ruzicka et al, 2007), DNA promoter methylation (Grayson et al, 2005;Abdolmaleky et al, 2005), and repressive histone modifications (Gavin et al, 2009a, b;Benes et al, 2007; in psychotic patients. These abnormalities are hypothesized to cause the muchreplicated reductions in GABAergic gene expression in psychosis (Benes et al, 2007;Akbarian et al, 1995;Fatemi et al, 2005;Hashimoto et al, 2008;Costa et al, 2004;Guidotti et al, 2000).…”
Section: Gadd45b and Psychosis Dp Gavin Et Almentioning
confidence: 99%
“…Unlike DNMT1, DNMT3A is overexpressed only in layers I and II (Zhubi et al, 2009). DNMT3B mRNA was examined and not detected in any cortical layer.…”
Section: Dnmts In Sz and Bp+mentioning
confidence: 99%